PENGARUH PERSEPSI SISWA TENTANG SUASANA KEHIDUPAN SEKOLAH TERHADAP MOTIF BERPRESTASI - Sisti Nurlina; Adang Hambali; Fridayanti Fridayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research based on phenomena about students whose positive and negative perception about school life. Those two perceptions are expected effecting achievement motive and effort in learning process. This quantitative research used caused and effect correlation. Population are 34 students from grade IX SMP Mika Bakti. Simple regression analysis is used to study the effect in this research. Statistical analysis result shows F value is 0.139 with significant level 0.712 (not significant) and probability value is 0,712 more than 0,05. It is concluded that student perception about school life does not significantly effect achievement motive on students at SMP IX Mika Bakti Ciparay.